THE RELATIONSHIP OF LEARNING INTEREST AND ENGINEERING IMAGES LEARNING OUTCOMES WITH FORMING AND ASSEMBLY LEARNING RESULTS IN CLASS XI METAL FABRICATION ENGINEERING EXPERTISE PROGRAM SMKN 1 LUBUK PAKAM - Efendi, Hidir; Syahputra, Dedi (Journal of Community Research and Service, 2019)
This study aims to determine the magnitude of (1) the relationship of learning interest with learning outcomes of formation and assembly (2) the relationship of learning outcomes of engineering drawing with learning outcomes of formation and assembly, (3) the relationship of interest in learning and learning outcomes of engineering drawing with learning outcomes of shaping and assembly. assembly. The population of this study was students of class XI majoring in Metal Fabrication Engineering at SMK Negeri 1 Lubuk Pakam, amounting to 36 people. Before this research was conducted, the instrument was tested on respondents who were not the research sample, namely the class XI students of SMK Negeri 1 Percut Sei Tuan, totaling 27 people. The research method used is correlational research. The research findings show that: (1) there is a relationship between interest in learning and learning outcomes of formation and assembly with a correlation coefficient of 0.719 with a coefficient of determination of 0.517. This means that 51.7% of learning outcomes of formation and assembly are determined by students' interest in learning. The coefficient of determination is also statistically significant which is indicated by a significance value of 0.000 which is below 0.05. 2) there is a significant relationship between the learning outcomes of engineering drawing and the learning outcomes of forming and assembling with a correlation coefficient of 0.598 with a coefficient of determination of 0.358. This means that 35.8% of the learning outcomes of constructing and fitting are determined by the learning outcomes of technical drawings. The coefficient of determination is also statistically significant which is indicated by a significance value of 0.000 which is below 0.05. (3) there is a relationship between interest in learning and learning outcomes of technical drawing together with learning outcomes of forming and assembly techniques with the regression equation obtained is . The results showed that interest in learning and learning outcomes of engineering drawings had a significant relationship with learning outcomes of forming and assembly techniques. This is indicated by the results of the F test where the calculated F value is 21.021 > 3.28 F table. Thus, there is a positive and significant relationship between interest in learning and learning outcomes of technical drawing together with learning outcomes of forming and assembling students of class XI of the Metal Fabrication skill program for students of SMK Negeri 1 Lubuk Pakam.